Modelling and Control of a Single-Wheel Inverted Pendulum by Using Adams and Matlab - Sinan ILGEN; Emre OFLAZ; Erdi Gülbahçe; Abdullah Çakan (International Journal of Applied Methods in Electronics and Computers, 2016)
This research is aimed at developing a multi-body simulation model and balancing control of a single-wheeled inverted pendulum. A virtual prototype of the system has been built by using Adams software and it is simulated in both Matlab and Adams software together. The Adams model has two inputs (disturbance and control) and two outputs (pendulum angle and wheel position).  Proportional-integral-derivative (PID) controller is designed and applied for balancing control and simulation of pendulum angle. The modelling and control results show that the Proportional-integral-derivative (PID) controller can successfully achieve balancing control of the single-wheeled inverted pendulum. Also this paper can make an important contribution to background of two-wheeled robots, self-balancing transportation devices.